Gerontic Nursing Care with Hypertension in Mrs. N by Soaking Feet Using Warm Water - Siti Sopiah, Nalla; Wahyudi, Iwan (CV. Literasi Publikasi Indonesia, 2025)
Hypertension, characterized by elevated blood pressure, is a prevalent cardiovascular disorder influenced by genetic, lifestyle, and socio-cultural factors. Effective management, including non-pharmacological interventions like warm water foot soaking therapy, is crucial to prevent complications. This case study details the nursing care provided to Mrs. N, a geriatric patient with hypertension, using warm water soaking therapy at Tarogong Health Center. A qualitative descriptive method was used to analyze the nursing process, covering assessment, diagnosis, intervention, implementation, and evaluation. The study identified three nursing problems: chronic pain, sleep pattern disturbance, and risk of falls. Warm water foot soaking therapy was implemented based on Evidence-Based Practice (EBP) to alleviate pain and improve peripheral circulation. Following three days of therapy, Mrs. N's blood pressure decreased. This study highlights the potential of warm water foot soaking therapy as a beneficial nursing intervention for managing hypertension in geriatric patients.